Some results on stability of retarded functional differential equations using dichotomic map techniques - Bená, Maria Aparecida; Dos Reis, José Geraldo [UNESP] (Springer Nature, 1998)
This paper deals with the study of the stability of nonautonomous retarded functional differential equations using the theory of dichotomic maps. After some preliminaries, we prove the theorems on simple and asymptotic stability. Some examples are given to illustrate the application of the method. Main results about asymptotic stability of the equation x′(t) = -b(t)x(t - r) and of its nonlinear generalization x′(t) = b(t) f (x(t - r)) are established. © 1998 Kluwer Academic Publishers.
Keywords: Asymptotic stability; Dichotomic maps; Retarded functional differential equation; Stability